Comparisons of the clinical outcomes of Centurion® active fluidics system with a low IOP setting and gravity fluidics system with a normal IOP setting for cataract patients with low corneal endothelial cell density - Liu, Yinan; Hong, Jing; Chen, Xiaoyong (Frontiers in Medicine, 2023)
Background: During cataract phacoemulsification surgery, the Alcon Centurion with Active Sentry can achieve a more stable anterior chamber, which allows a lower intraocular pressure (IOP) setting than the gravity fluidics system. In this randomized controlled trial, we compared these two systems’ damage to the cornea under different IOP settings. Methods: Seventy-eight eyes of 53 patients with corneal endothelial cell density (ECD) of 500~1500 /mm2 were enrolled and randomly divided into the active fluidics system (AFS) group using an Active Sentry handpiece with 30 mmHg IOP setting (40 eyes) and the gravity fluidics system (GFS) group using an Ozil handpiece with 80 cmH2O IOP setting (38 eyes). Intraoperative parameters, visual acuity, corneal edema ratio, central corneal thickness (CCT) changes as well as loss rate of ECD were analyzed. Results: We observed no significant differences in best corrected visual acuity (BCVA), cumulative dissipated energy (CDE), total case time, estimated fluidics usage (EFU) and ophthalmic viscoelastic devices (OVDs) usage between the two groups. The enrolled eyes were further divided into soft nucleus (27 eyes) and hard nucleus (51 eyes) subgroups. And we found less pain complaint during surgeries, lower corneal edema ratio at 1-day and 1-week visit, smaller CCT changes at 1-day visit and lower ECD loss rate at 1-month visit (p<0.05) in both subgroups of the AFS group than in the GFS group, implying higher intraoperative comfort levels and less corneal damage of the AFS group with a low IOP setting. Conclusion: Owing to a lower IOP setting, Centurion® Vision System with Active Sentry handpiece causes less corneal damage and pain perception during phacoemulsification for patients with low preoperative ECD.